On Myopic Equilibria in Dynamic Games with Endogenous Discounting - Bolt, Wilko; Tieman, Alexander (Washington, D.C. : International Monetary Fund, 2006)
This paper derives an equilibrium for a competitive multi-stage game in which an agents' current action influences his probability of survival into the next round of play. This is directly relevant in banking, where a banks' current lending and pricing decisions determines its future probability of default. In technical terms, our innovation is to consider a multi-stage game with endogenous discounting. An equilibrium for such a multi-stage game with endogenous discounting has not been derived before in the literature.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: WP